Spin-orbit and anisotropic strain effects on the electronic correlations in Sr2RuO4 - Facio, Jorge Ismael (2018)
We present an implementation of the rotationally invariant slave boson technique as an impurity solver for density functional theory plus dynamical mean field theory (DFT+DMFT). Our approach provides explicit relations between quantities in the local correlated subspace treated with DMFT and the Bloch basis used to solve the DFT equations. In particular, we present an expression for the mass enhancement of the quasiparticle states in reciprocal space. We apply the method to the study of the electronic correlations in Sr2RuO4 under anisotropic strain. We find that the spin-orbit coupling plays a crucial role in the mass enhancement differentiation between the quasi-one-dimensional α and β bands, and on its momentum dependence over the Fermi surface. The mass enhancement, however, is only weakly affected by either uniaxial or biaxial strain, even across the Lifshitz transition induced by the strain.